TLR4 activation by lysozyme induces pain without inflammation - Yadav, Saurabh; Singh, Amrita; Kant, Ravi; Surolia, Avadhesha (Frontiers in Immunology, 2023)
Mostly, pain has been studied in association with inflammation, until recent studies which indicate that during bacterial infections, pain mechanisms could be independent of the inflammation. Chronic pain can sustain long after the healing from the injury, even in the absence of any visible inflammation. However, the mechanism behind this is not known. We tested inflammation in lysozyme-injected mice foot paw. Interestingly, we observed no inflammation in mice foot paw. Yet, lysozyme injections induced pain in these mice. Lysozyme induces pain in a TLR4-dependent manner and TLR4 activation by its ligands such as LPS leads to inflammatory response. We compared the intracellular signaling of MyD88 and TRIF pathways upon TLR4 activation by lysozyme and LPS to understand the underlying mechanism behind the absence of an inflammatory response upon lysozyme treatment. We observed a TLR4 induced selective TRIF and not MyD88 pathway activation upon lysozyme treatment. This is unlike any other previously known endogenous TLR4 activators. A selective activation of TRIF pathway by lysozyme induces weak inflammatory cytokine response devoid of inflammation. However, lysozyme activates glutamate oxaloacetate transaminase-2 (GOT2) in neurons in a TRIF-dependent manner, resulting in enhanced glutamate response. We propose that this enhanced glutaminergic response could lead to neuronal activation resulting in pain sensation upon lysozyme injections. Collectively we identify that TLR4 activation by lysozyme can induce pain in absence of a significant inflammation. Also, unlike other known TLR4 endogenous activators, lysozyme does not activate MyD88 signaling. These findings uncover a mechanism of selective activation of TRIF pathway by TLR4. This selective TRIF activation induces pain with negligible inflammation, constituting a chronic pain homeostatic mechanism.